2022
DOI: 10.1111/tbed.14753
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii infection in sheep and goats from different geographical regions of the world: Systematic review and meta‐analysis

Abstract: The Toxoplasma gondii is an obligate intracellular protozoan parasite which significantly impact small ruminant productivity, international animal trade and transboundary movement of animal across the globe. The seroprevalence of T. gondii infection (toxoplasmosis) in sheep and goats is widely studied in many parts of the world and there is a lack of comprehensive information on prevalence estimates considering the global and regional perspectives. The aim of the study was to use systematic review and metaanal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 203 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Ewes had a significantly higher seroprevalence than male sheep in one study [43], most likely because male sheep have a more robust immune response against the parasite due to hormonal differences [72][73][74]. This finding agrees with a recent meta-analysis on sheep T. gondii seroprevalence and associated risk factors [71]. Regarding rams, sexual transmission is possible, and an experimental study demonstrated that T. gondii reduces the quality parameters of sperm (viability, motility, velocity), while sulphadimidine treatment did not revert the sperm cell morphological abnormalities [75].…”
Section: Sheep and Meat Thereofsupporting
confidence: 88%
See 2 more Smart Citations
“…Ewes had a significantly higher seroprevalence than male sheep in one study [43], most likely because male sheep have a more robust immune response against the parasite due to hormonal differences [72][73][74]. This finding agrees with a recent meta-analysis on sheep T. gondii seroprevalence and associated risk factors [71]. Regarding rams, sexual transmission is possible, and an experimental study demonstrated that T. gondii reduces the quality parameters of sperm (viability, motility, velocity), while sulphadimidine treatment did not revert the sperm cell morphological abnormalities [75].…”
Section: Sheep and Meat Thereofsupporting
confidence: 88%
“…Estimations ranged from 23% in Crete in 1995 [48] to 90% in Trikala in 2019 [44], with most studies finding seropositivity of around 50% and an upward trend throughout the years, as seen in Table 1. Compared to the global pooled seroprevalence in sheep at 33.86% and the pooled European seroprevalence at 41.01% [71], it becomes evident that Greece has higher seroprevalence and is endemic for ovine toxoplasmosis.…”
Section: Sheep and Meat Thereofmentioning
confidence: 89%
See 1 more Smart Citation
“…Toxoplasma gondii ( T. gondii ) is an opportunistic intracellular parasitic protozoan that can infect intermediate hosts (including humans, ruminants, rodents, and birds) [ [1] , [2] , [3] , [4] , [5] , [6] ]. This parasite has been reported even in cold-blooded animals and they can act as the source of infection for the various hosts that feed on them [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the causes of abortion and stillbirth when the first infection occurs. The disease is a major cause of abortion in sheep and goats in Uruguay, New Zealand, the United Kingdom and Australia (Dubey, 2003;Ahaduzzaman & Hasan, 2022).…”
Section: Introductionmentioning
confidence: 99%